Farm Households’ Livelihood Diversification into Agro-processing and Non-agro-processing Activities: Empirical Evidence from Ghana - Kuwornu, John K.M.; ., Moses Dumayiri (Information Management and Business Review, 2014)
This study seeks to identify the types of agro-processing and non-agro-processing activities in the Upper West Region of Ghana and the factors influencing households’ choice of diversification into each of these groups of activities as livelihood strategies. The study employs the multinomial logit model to identify the determinants of diversification. Data were obtained from a survey conducted by the International Food Policy Research Institute (IFPRI) in December, 2012 covering production activities for the 2011 agricultural year. The Primary data were collected from two hundred and fifty (250) food crop farmers selected using a multistage sampling procedure. The empirical results indicate that households in the Upper West Region diversify their livelihoods activities to agro-processing and activities not related to agro-processing. Households who are likely to diversify are females who are high income earners with small farm sizes. Further, educated and asset-rich farmers who produce for subsistence only are more likely to diversify to agro-processing while access to credit will influence diversification but not necessarily into agro-processing. These results have implications for the development of agro-processing ventures in developing countries.